Introductory Raman spectroscopy - Ferraro, John R., 1918- (Academic Press, 2003)
This second edition of Introductory Raman Spectroscopy serves as a guide to newcomers who wish to become acquainted with this dynamic technique. Written by three acknowledged experts this title uses examples to illustrate the usefulness of the technique of Raman spectroscopy in such diverse areas as forensic science, biochemistry, medical, pharmaceutical prescription and illicit drugs. The technique also has many uses in industry. Updated Applications chapter Demonstrated the versatility and utility of Raman spectroscopy in problem solving in science Serves as an excellent reference text for both beginners and more advanced students Discusses new applications of Raman spectroscopy in industry and research.